2022
DOI: 10.1002/aenm.202203189
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Zinc‐Derived Dendrite and Its Suppression in Mildly Acidic Aqueous Zinc‐Ion Battery

Abstract: Aqueous zinc‐ion batteries (ZIBs) are attractive in energy storage due to the use of aqueous electrolytes that ensures safety and ease of handling all parts in air. However, catastrophic zinc dendritic growth on zinc metal anodes impedes their practical application. Herein, Zn3(PO4)3·4H2O (ZP)‐coated zinc metal anode is introduced to effectively suppress the dendrite growth and the chemical state of the dendrites that are composed of metallic Zn0, ZnO, and Zn(OH)2 is elucidated first. Significant improvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 63 publications
1
28
1
Order By: Relevance
“…X-ray diffraction (XRD) was performed on the Zn plates after a prolonged store time of 18 days (Figure S24, Supporting Information), it is revealed that xZnCO 3 •yZn(OH) 2 •zH 2 O, rather than the popularly observed Zn x OTf y (OH) 2x−y •nH 2 O (ZOTH), was formed for Zn soaked in 3 m Zn(OTf) 2 . [5,7,10,33] And, contrary to our expectations, in IL-AE the thin passivation layer is identified as ZOTH. This result does not undermine the general conclusion that ZOTH is detrimental to Zn reversibility, but provides a new thought about the role of ZOTH that, under certain conditions, a uniform ZOTH may contribute to the enhanced Zn stability against the electrolyte.…”
Section: Resultscontrasting
confidence: 99%
“…X-ray diffraction (XRD) was performed on the Zn plates after a prolonged store time of 18 days (Figure S24, Supporting Information), it is revealed that xZnCO 3 •yZn(OH) 2 •zH 2 O, rather than the popularly observed Zn x OTf y (OH) 2x−y •nH 2 O (ZOTH), was formed for Zn soaked in 3 m Zn(OTf) 2 . [5,7,10,33] And, contrary to our expectations, in IL-AE the thin passivation layer is identified as ZOTH. This result does not undermine the general conclusion that ZOTH is detrimental to Zn reversibility, but provides a new thought about the role of ZOTH that, under certain conditions, a uniform ZOTH may contribute to the enhanced Zn stability against the electrolyte.…”
Section: Resultscontrasting
confidence: 99%
“…The chemical composition of the ZPO layer is verified by X-ray photoelectron spectra (XPS). In the Zn 2p spectrum (Figure i), the peak at 1022.1 eV originates from the Zn–O bond. , In the P 2p spectrum (Figure j), the peak at 133.4 eV comes from the P–O bond. , After Ar-ion sputtering, two peaks remain almost the same, excluding the simple adsorption of ZPO on Zn foils. In the XRD patterns (Figure S4a), the Zn(002) texture becomes more and more obvious when the annealing temperature increases from room temperature to 415 °C.…”
Section: Resultsmentioning
confidence: 95%
“…In addition to the Zn electrodeposition mechanism discussed earlier, high current density operations have a significant impact on suppressing the HER and subsequently on the generation of LDH species. [39][40][41][42] At higher current densities, a more uniform Zn electrodeposition layer is formed on current collectors, such as Cu, SS, and Ti substrates, which triggers the severe HER on the surface, as per the classic hydrogen evolution materials' volcano curve (Fig. 6b).…”
Section: Critical Role Of the Hydrogen Evolution Reactionmentioning
confidence: 99%